2014
DOI: 10.1105/tpc.113.121111
|View full text |Cite
|
Sign up to set email alerts
|

The bHLH Transcription Factor HBI1 Mediates the Trade-Off between Growth and Pathogen-Associated Molecular Pattern–Triggered Immunity inArabidopsis   

Abstract: The trade-off between growth and immunity is crucial for survival in plants. However, the mechanism underlying growthimmunity balance has remained elusive. The PRE-IBH1-HBI1 tripartite helix-loop-helix/basic helix-loop-helix module is part of a central transcription network that mediates growth regulation by several hormonal and environmental signals. Here, genome-wide analyses of HBI1 target genes show that HBI1 regulates both overlapping and unique targets compared with other DNA binding components of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
165
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(180 citation statements)
references
References 70 publications
8
165
0
Order By: Relevance
“…Mitochondria dysfunction interferes with 9-LOX and BR signaling (Bekh-Ochir et al, 2013;Vellosillo et al, 2013) and might unbalance ROS production, a key process in the control of plant development and plant defense. Recent studies indicate BR pathway involvement in plant immunity and its role in balancing defense versus growth (Belkhadir et al, 2014;Fan et al, 2014). Our results show the sequential participation of the 9-LOX and BR pathways in triggering cell wallbased plant defense; in response to pathogen inoculation, oxylipins might function as ROS signals to activate the BR pathway and contribute to cell wall reinforcement and plant defense.…”
Section: Discussionmentioning
confidence: 77%
“…Mitochondria dysfunction interferes with 9-LOX and BR signaling (Bekh-Ochir et al, 2013;Vellosillo et al, 2013) and might unbalance ROS production, a key process in the control of plant development and plant defense. Recent studies indicate BR pathway involvement in plant immunity and its role in balancing defense versus growth (Belkhadir et al, 2014;Fan et al, 2014). Our results show the sequential participation of the 9-LOX and BR pathways in triggering cell wallbased plant defense; in response to pathogen inoculation, oxylipins might function as ROS signals to activate the BR pathway and contribute to cell wall reinforcement and plant defense.…”
Section: Discussionmentioning
confidence: 77%
“…Due to the sessile lifestyle of plants and the limitation of available energy, plants have evolved an elaborate regulatory network to effect a tradeoff between growth and immune responses to ensure plant survival under fluctuating environments (Kazan and Manners, 2009;Fan et al, 2014). V. dahliae is notorious for its infection strategies and great genetic plasticity, and it causes significant economic losses for a broad range of crops, such as cotton, strawberry (Fragaria 3 ananassa), oilseed rape (Brassica napus), tomato (Solanum lycopersicum), and Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…RIN4 is a known target of multiple effectors (Jones and Dangl, 2006). HBI1 is a basic helix-loop-helix TF that mediates the tradeoff between plant growth and the immune response (Fan et al, 2014). Functional enrichment analysis indicated that development and defense are the most prominent themes in this subnetwork.…”
Section: Identification Of a Shared Subnetwork Between Pti And Etimentioning
confidence: 99%